2009
DOI: 10.5194/acp-9-6157-2009
|View full text |Cite
|
Sign up to set email alerts
|

An overview of two years of ozone radio soundings over Cotonou as part of AMMA

Abstract: Abstract. As part of the African Monsoon Multidisciplinary Analysis (AMMA) program, a total of 98 ozone vertical profiles over Cotonou, Benin, have been measured during a 26 month period (December 2004-January 2007. These regular measurements broadly document the seasonal and interannual variability of ozone in both the troposphere and the lower stratosphere over West Africa for the first time. This data set is complementary to the MOZAIC observations made from Lagos between 0 and 12 km during the period 1998-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 68 publications
5
73
0
Order By: Relevance
“…A combination of modelling, in situ and remote sensing observations indicates that enhancements of O 3 and CO in the troposphere over Africa can result from the transport of biomass burning emissions from fires situated in the opposite dry-season hemisphere add (Barret et al, 2008;Sauvage et al, 2005;Thouret et al, 2009;Real et al, 2010). High acetonitrile observations provided clear evidence of biomass burning outflow during three flights on which the PTR-MS was operated.…”
Section: Flights In Biomass Burning Outflowmentioning
confidence: 89%
See 1 more Smart Citation
“…A combination of modelling, in situ and remote sensing observations indicates that enhancements of O 3 and CO in the troposphere over Africa can result from the transport of biomass burning emissions from fires situated in the opposite dry-season hemisphere add (Barret et al, 2008;Sauvage et al, 2005;Thouret et al, 2009;Real et al, 2010). High acetonitrile observations provided clear evidence of biomass burning outflow during three flights on which the PTR-MS was operated.…”
Section: Flights In Biomass Burning Outflowmentioning
confidence: 89%
“…Crutzen and Andreae, 1990), and VOC such as acetonitrile can serve as tracers of biomass burning influence. This is particularly useful in West Africa, where observations of enhanced O 3 and CO in the mid-troposphere during the wet season have been attributed to long range transport from fires across the equator (Sauvage et al, 2005;Thouret et al, 2009) Published by Copernicus Publications on behalf of the European Geosciences Union. 5282 J. G. Murphy et al: Measurements of volatile organic compounds over West Africa but back trajectories struggle to represent these transport patterns .…”
Section: Introductionmentioning
confidence: 99%
“…For example, over Lagos, Nigeria, ozone-enhanced layers are observed in December-February, when burning occurs regionally, and also in July-August, when biomass burning occurs over southern equatorial Africa (Sauvage et al, , 2007b. Such processes have been further investigated in the frame of AMMA (Reeves et al, 2010;Thouret et al, 2009;Mari et al, 2008). Similarly, over Brazzaville, the seasonal cycle of ozone peaks in July-August but a secondary maximum appears in January-February due to transport of ozone and precursors from fires occurring in the Northern Hemisphere (Sauvage et al, , 2007b.…”
Section: Biomass Burningmentioning
confidence: 99%
“…Reeves et al (2010) provide a clear characterisation of the ozone distribution throughout the troposphere over West Africa during the monsoon period. Owing to previous analysis based on MOZAIC data (Sauvage et al, 2007a and the regular ozone soundings over Cotonou over 2 years (Thouret et al, 2009), it has been shown that the biomass burning seasons in both hemispheres impact the tropospheric ozone profiles in both hemispheres as well. As a consequence, a picture like the so-called "ozone paradox" (Thompson and Hudson, 1999) was shown to be no longer valid (Sauvage et al, 2006) owing to the insight provided by additional in situ observations.…”
Section: Atmosmentioning
confidence: 99%
“…In the frame of AMMA, an ozone sounding station was set up in Cotonou, Benin (6.21 • N, 2.23 • E) thanks to the IRD (Institut de Recherche et Développement) and the SMN/ASECNA (Service Météorologique National/Agence de securité et de navigation aérienne) people located there. These regular soundings were performed between December 2004 and January 2007 and aimed to better assess the seasonal and interannual variability of ozone vertical profiles in Equatorial Africa as described by Thouret et al (2009). They found that December 2005 was characterized by very high ozone concentrations throughout the troposphere compared to the rest of the sampled period.…”
Section: Introductionmentioning
confidence: 99%